Determination of genetic stability in Kelampayan plantlets regenerated from tissue culture using RAPD markers - Flora, Anak Lapik (Universiti Malaysia Sarawak (UNIMAS), 2012)
Kelampayan species from the family of Rubiaceae was studied in terms of its ability to conserve genetic stability throughout plantlets regeneration from tissue culture specifically by organogenesis, via the culturing of nodal segments and shoot tips. The assessment of genetic stability had been carried out through the employment of Inter-Simple Sequence Repeats (ISSR) Marker. Two ISSR primers had been selected, namely (ACC)6G and (AG)9C as these primers were capable of producing informative and reproducible outcome. Based on the ISSR band data, a total of 37 loci were generated. The binary data matrix based on the Jaccard’s similarity coefficient was calculated, resulting to a similarity indices ranged from 0.14 to 0.95 while the Shannon’s information index had indicated a value of 0.3431. 100% polymorphic loci had also been revealed. Additionally, the neighbor-joining tree constructed based on DSA shared allele had implied similar result as UPGMA dendrogram, signifying a relatively distant relationship among kelampayan plantlets and its maternal genotype. The high level of genetic variation detected at the early stage of culturing had shown to be as a result of mislabeling of samples during subculturing process. These had ultimately proven the effectiveness of ISSR markers as reliable tools for genetic variation studies, and thus indicated that kelampayan plantlets regenerated from tissue culture in this study is genetically unstable.